2016
DOI: 10.1111/1541-4337.12238
|View full text |Cite
|
Sign up to set email alerts
|

Applications of Wine Pomace in the Food Industry: Approaches and Functions

Abstract: Winemaking generates large amounts of wine pomace, also called grape pomace. This by-product has attracted the attention of food scientists and the food industry, due to its high content in nutrients and bioactive compounds. This review mainly focuses on the different published approaches to the use of wine pomace and its functions in the food industry. Traditionally, wine pomace has been used to obtain wine alcohol, food colorings, and grape seed oil. More recently, research has focused in the production of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
191
0
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 268 publications
(244 citation statements)
references
References 280 publications
1
191
0
7
Order By: Relevance
“…[9][10][11]17] Therefore, wine pomace and grape seeds as the dominant part of it, represent valuable source of these bioactive compounds that are used in numerous types of products in food and pharmaceutical industry. [18] Therefore, the adequate amount of raw material could be of importance implicating that one of the parameters for selecting the appropriate clone is also number of seeds per berry. In previous research on ampelographic characterization of Prokupac clones, high level of morphological variation was noticed, where the most significant variation was found in the number of berry seeds ranging from 1.27 to 3.28.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9][10][11]17] Therefore, wine pomace and grape seeds as the dominant part of it, represent valuable source of these bioactive compounds that are used in numerous types of products in food and pharmaceutical industry. [18] Therefore, the adequate amount of raw material could be of importance implicating that one of the parameters for selecting the appropriate clone is also number of seeds per berry. In previous research on ampelographic characterization of Prokupac clones, high level of morphological variation was noticed, where the most significant variation was found in the number of berry seeds ranging from 1.27 to 3.28.…”
Section: Resultsmentioning
confidence: 99%
“…Linoleic acid, as one of the essential fatty acids, plays an important role in human diet, thus oil abundant in these fatty acids are highly appreciated because of its nutritional and medicinal properties. [18] High levels of unsaturated fatty acids accompanied with lower, but significant content of saturated fatty acids in grape seed oil makes it suitable for cooking food at middle to high temperature due to its high smoking point. [20,23] Also, oils that possess high content of linoleic acids are preferable for usage in cosmetic industry, especially for dermatological products intended for care of oil and problematic skin prone to pore clogging.…”
Section: Resultsmentioning
confidence: 99%
“…Grape ( Vitis spp.) is one of the most valued fruits consumed and industrialized in the world (García‐Lomillo & González‐SanJosé, ). According to the FAO (), 50 million tons are produced worldwide every year, with 75% of it being used in wine‐making.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some studies have shown the use of grape peel in products as a source of phenolic compounds, such as cereal products (cereal bars, muffins, biscuits), bread, dairy products (cheese, yogurt), as well as seafood, purees, and infusions (García‐Lomillo & González‐SanJosé, ), while grape peel extracts can be used in beverages and dehydrated fruit as a functional supplement to increment their phenolic content (Pedroza, Carmona, Pardo, Salinas, & Zalacain, ; Rózek, Achaerandio, Güell, López, & Ferrando, ). Some authors have demonstrated the versatility of grape pomace extracts as preservatives (antioxidant activity) in meat products (García‐Lomillo & González‐SanJosé, ; Shirahigue et al, ) and/or as antimicrobials against different foodborne pathogens (Xu et al, ). In many cases, the incorporation of by‐products/extracts increases the acceptability of products by the consumers due to sensory repercussion, such as color, odor, bitter and astringent taste perception, antipolyphenol oxidase activity, reduction of residual nitrites, and nitrosamines (Acun & Gül, ; García‐Lomillo & González‐SanJosé, ; Shirahigue et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…The residue may represent from 13.5 to 14.5% at the total volume of grapes, and may reach 20% (Ahmad & Ali Siahsor, ; Rockenbach et al, ). The most abundant phenolic compounds in wine pomace are anthocyanins concentrated in the skin, and flavonols present mostly in the grape seed (56–65% total flavonol) (García‐Lomillo & González‐SanJosé ). Skins and seeds of grapes are produced in large quantities by the winemaking industry.…”
Section: Introductionmentioning
confidence: 99%